2021
DOI: 10.1186/s12876-021-01683-y
|View full text |Cite
|
Sign up to set email alerts
|

Collision of Epstein–Barr virus-positive and -negative gastric cancer, diagnosed by molecular analysis: a case report

Abstract: Background Epstein–Barr virus (EBV)-positive gastric carcinoma (GC) is defined by the proliferation of GC cells with EBV infection. The co-existence of EBV-positive and -negative components in a single GC is rare. We report a case of GC with the co-existence of EBV-positive and EBV-negative components, in which we performed—for the first time—various molecular analyses to elucidate their histogenesis. Case presentation An 81-year-old man was diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The HER2 status of a tumor also varies at different sites [37], so it is also possible that different molecular subtypes exist within a tumor. In addition to our data suggesting that heterogeneity of molecular subtypes according to TCGA definition is a common phenomenon, there are already case reports in which intra‐tumoral heterogeneity has been observed for EBV [36,38] or MSI [39,40]. Although GC heterogeneity is known, its detection is still challenging in the laboratory and deep learning could help.…”
Section: Resultsmentioning
confidence: 59%
“…The HER2 status of a tumor also varies at different sites [37], so it is also possible that different molecular subtypes exist within a tumor. In addition to our data suggesting that heterogeneity of molecular subtypes according to TCGA definition is a common phenomenon, there are already case reports in which intra‐tumoral heterogeneity has been observed for EBV [36,38] or MSI [39,40]. Although GC heterogeneity is known, its detection is still challenging in the laboratory and deep learning could help.…”
Section: Resultsmentioning
confidence: 59%
“…Since the tumor had EBV- positive and -negative areas at each side with distinct histology and p53 immunostaining pattern, we first considered this case as EBV collision gastric cancer. EBV collision gastric cancers have been rarely reported in the scientific literature [ 6 9 ]. Intratumoral heterogeneity of EBVaGCs have been reported in a few previous studies [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, EBV collision gastric cancer, unlike gastric cancer with heterogeneous EBV positivity, has distinct tumor components at the border that exhibit EBV positivity and negativity, rather than having two intermixed components. Miyabe et al suggested that EBV-positive and -negative collision gastric cancers have different histogenesis based on the result of TP53 sequencing, targeted next-generation sequencing, and HER2 and C-MYC fluorescence in situ hybridization (FISH) study [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another genetic feature of EBV (+) GC is lack of TP53 mutations. The TP53 tumor suppressor is the most recurrently mutated gene in GC; however, TP53 mutations are not frequent in EBV (+) GC among the GC subtypes classified by TCGA [1,23,24].…”
Section: Somatic Mutationsmentioning
confidence: 99%